“Narrow AI” in the Context of AI Implementation, Transformation and the End of Some Jobs - Todorova, Mariana (Research Papers, 2021)
The article reviews how the appearance of the “artificial narrow intelligence”, which is already a fact, will participate in the processes of the transformation, the disappearance of some jobs and the creation of others. The aim of the text is to reveal two scenarios: optimistic and pessimistic as well as the basic theses in the debate of these problems. The tasks of the article are to draw the chances and to warn for the risks at the same time that follow of the implementation of AI in different human realms. The methodology of the research includes: a comparative analysis, key trends tracking, building of two alternative scenario forecasts.The originality of the text contains in the concrete placement of the Narrow AI in the context of the transformation of one the key human activity as labor is.